Worldwide 1st MED-EL Mi1200 SYNCHRONY cochlear implant magnet removal for MRI image artifact reduction - Stefan Wieser; Isabel Igerc; Klaus Hausegger; Hans Eckel (Otolaryngology Case Reports, 2018)
A 51-years-old male unilateral cochlear implant recipient underwent a magnet removal surgery 7 months after left ear MED-EL Mi1200 SYNCHRONY implantation, in order to reduce image artifact during magnet resonance imaging of neurofibromatosis 2 tumor progression. The implant magnet was removed under local anesthesia with the Magnet Removal Tool and the non-magnetic spacer was inserted with the Magnet Insertion Tool within 20 min. After the painless 1.5 hours MRI procedure the non-magnetic spacer was exchanged against the replacement implant magnet within 15 min. This is the first known published case of magnet removal from a MED-EL Mi1200 SYNCHRONY. Keywords: Cochlear implant, Implant, Radiology, Magnetic resonance imaging